Pengenalan dan Pelatihan Komponen Robot Transporter bagi Siswa Siswi SMA Kesatrian 2 Semarang - Sulistyo, Isya' Aryan; Hilal, Yusuf Nurul; Derman, Derman; Suryawani, Indri (Jurnal Pengabdian KOLABORATIF, 2026)
In the current era of Industry 4.0, technological and robotics advancements are proceeding rapidly, particularly in the fields of science, technology, and mathematics; however, knowledge and literacy among high school students regarding the identification and use of robotic components remain very limited. An introductory training session on transporter robot components was conducted for students at SMA Kesatrian 2 Semarang with the aim of enhancing their understanding of robotics fundamentals. The activity involved the presentation of material, demonstrations, and hands-on practice in identifying the parts of a transporter robot. Assessment was carried out using pre-tests and post-tests administered to 20 participants. The results demonstrated a significant improvement in understanding across all areas, including robot components, power sources, drive systems, control systems, and the functions of the transporter robot. The average percentage of correct answers rose from 24% in the pre-test to 85% in the post-test. These results indicate that the training successfully improved student understanding and fostered greater interest in robotics technology.